Intrigue box set June 2023 - Daniels, B. J. (Sydney, NSW : HarperCollins Publishers, 2023)
"Danger In The Nevada Desert: Denise N. Wheatley: With a serial killer terrorising her desert town, Sergeant Charlotte Bowman needs the savviest partner she can find - fast! Enter hotshot California detective Miles Love. Together Charlotte and Miles make a formidable team despite their fiery past. But with the stakes as intense as their chemistry, can the pair outwit a ruthless murderer - who might just have River Valley's newest sergeant next in his sights?" -- Publisher website.
"Dead Again - Nichole Severn: Detective Riggs Karig has never forgotten his childhood best friend. Now he's found her again, and he wants to know how she's involved in his partner's death. He soon discovers that Macie Barclay is a target, not a suspect - and that she knows more about the case he's working than he does. Can they put their past behind them to save an innocent life?" -- Publisher website.
"Her Brand Of Justice - B.J. Daniels: Ansley Brookshire's search for her birth mother takes her from the gated estate where she grew up to Lonesome, Montana. This is where she meets Buck Crawford. Determined to help, the gorgeous rancher introduces her to Colt Brothers Investigations. But someone wants the secrets surrounding her adoption to stay buried - and they'll do anything to keep her from uncovering the truth..." -- Publisher website.
"Ozarks Double Homicide - Maggie Wells: Michelle Fraser's undercover probe into a prestigious law firm has hit a snag. After years accumulating evidence, the murder of two partners threatens the FBI operative's assignment. Tasked with defending the prime suspect, she's torn between helping investigator Ethan Scott and preserving her cover. Ethan senses Michelle isn't what she seems. But as the case heats up, can Michelle trust Ethan with her secret?" -- Publisher website.
"Trapped In Texas - Barb Han: Security expert Sean Hayes would rather take a case than return to his family's Texas ranch. But finding Raelynn Simmons leads a stalker right to her - and forces Sean and the pretty singer into hiding. As they race to identify the threat, Sean must resist their instant attraction. But will a lethal endgame separate them for good?" -- Publisher website.
"Wyoming Mountain Murder - Juno Rushdan: When self-defence trainer Charlie Sharp is nearly killed by an explosion, Wyoming detective Brian Bradshaw finds himself with a murder investigation on his hands. And worse, it involves one of his own. Now bodies are turning up, and Brian suspects Charlie knows more than she's telling. Trusting each other is hard enough. But knowing her secrets might be more danger than he bargained for..." -- Publisher website.
General.
Mode of Access: Available online.
Keywords: Contemporary romance; Fiction - Mystery & Detective - Police Procedural; Fiction - Thrillers; Electronic books; Romance fiction